2014
DOI: 10.5005/jp-journals-10015-1292
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Oral Health Awareness among the Final Year Undergraduate Nursing Students in Abha, Saudi Arabia

Abstract: Background and aim: Nurses have first level of contact with patients and their attendants. The services of nurses are also required in promoting the oral health knowledge among the general public. Thus, the aim of this study is to assess the oral health awareness of all the final year undergraduate nursing students in Abha, Saudi Arabia. Materials and methods: A questionnaire based study was con ducted in Abha, in which for a total of 204 final year under graduate nursing students who gathered on the day of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…However, Muttineni et al [ 14 ] in their study of 147 final year nursing students in India concluded that nursing students had adequate basic knowledge of oral health but were still deficient in correct brushing techniques. Similar findings were also reported by Asif et al [ 18 ] amongst nursing students. With the poor awareness of oral health among the medical doctors, nurses and their students in different part of the world, it became necessary to consider this aspect of health care especially in this part of the world where there are limited resources.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, Muttineni et al [ 14 ] in their study of 147 final year nursing students in India concluded that nursing students had adequate basic knowledge of oral health but were still deficient in correct brushing techniques. Similar findings were also reported by Asif et al [ 18 ] amongst nursing students. With the poor awareness of oral health among the medical doctors, nurses and their students in different part of the world, it became necessary to consider this aspect of health care especially in this part of the world where there are limited resources.…”
Section: Introductionsupporting
confidence: 92%
“…This findings is similar to the reports of Chandra et al [ 22 ] where 100% of participants of high socio economic status group claimed they are awareness of dental diseases. Similarly, Asif et al [ 18 ] also found that 89.9% of their study population knew that there were 32 teeth in the adult cavity. The increased awareness in this study may be due to the fact that the study was done among the educated/professionals.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Oral hygiene practices were satisfactory showing 58.5% was brushing their teeth twice daily, this may be as the study was conducted in educated professionals whereas other studies[ 13 14 15 ] show brushing once daily. Despite that only 33.3% were aware of appropriate time for routine dental consultation thus showing a lack of knowledge.…”
Section: Discussionmentioning
confidence: 77%